Relationship between joint torque of support leg and ground reaction force in side-step cutting - Suzuki, Y.; Ae, M.; Takenaka, S.; Kobayashi, Y.; Fujii, N. (ISBS - Conference Proceedings Archive (Konstanz), 2013)
The purpose of this study was to investigate the relationship between the joint torque of the support leg and the ground reaction force in the side-step cutting technique. The ground reaction forces and three-dimensional kinematics of the side-step cutting motion with 90° direction change were collected from 20 male university ball-game players. The angular impulses of the knee and ankle extension torques were correlated with the impulses of the inward, backward, and forward ground reaction forces. These results indicate that the knee and ankle contributed to change the horizontal velocity of the center of mass. Although the angular impulses of the hip joint did not correlate with the impulses of the ground reaction forces, the hip exerted large extension and adduction torques immediately after the foot strike. This implies the hip contributed to maintain the body`s position and balance rather than to change the velocity of the center of mass.